Health System Needs to Establish Cardiac Surgery Centers - Vervoort, Dominique; Premkumar, Akash; Ghandour, Hiba; Kpodonu, Jacques (The Thoracic and Cardiovascular Surgeon, 2021)
Cardiovascular diseases are the leading cause of mortality worldwide, responsible for nearly 18 million deaths each year. More than 80% of these take place in low- and middle-income countries (LMICs), where access to cardiac surgical services is scarce. Approximately 93% of the LMIC population, or six billion people worldwide, are estimated to lack access to safe, timely, and affordable cardiac surgical care as a result of workforce, infrastructure, financial, and quality barriers. Various models have been proposed and attempted to establish cardiac surgery centers in LMICs; however, only some have been successful in achieving sustainable local services. Here, we describe the workforce, infrastructure, financial, and political needs and considerations from a health systems perspective to establish a cardiac surgery center.
Keywords: health system; cardiac surgery; health policies